Gdańsk carillon tablatures - Popinigis, Danuta (Interdisciplinary Studies in Musicology, 2018)
The music collections of Gdańsk State Archive include music written for the automatic carillon of Gdańsk Main Town Hall. These are four tablatures with a unique notation system that appears only in Gdańsk sources. The oldest tablature (consisting of four volumes) was produced in the years 1769-1775; two others (one volume each) were copied in 1775 and 1776; the fourth was compiled in the years 1808-1812. The tablatures contain a total of 653 chorale settings. Their author was Theodor Friedrich Giilich, who programmed the Town Hall carillon from 1764 to 1776. The Main Town Hall carillon played the chorales every hour. Two different chorales could be programmed on the carillon drum simultaneously. A longer chorale signalled the passing of an even-numbered hour and a shorter chorale an odd-numbered hour. The chorales were changed every Saturday. The four-volume tablature contains chorale settings for the whole year, settings of funeral hymns and instructions for changing the chorales on the carillon drum and programming chorales for special occasions (such as the arrival of the king, the death of a prominent figure, such as the monarch, the mayor, a city councillor or a councillor’s wife, and elections to the City Council, as well as the opening and closing of St Dominic’s Fair). One of the single-volume tablatures includes Old Lutheran Church songs, another has Reformed Evangelical Church songs, and the fourth tablature contains chorales arranged for successive weeks of the year. This article presents the Gdańsk carillon tablatures and explains the principles behind their musical notation.